Comparison of unintended and intended pregnancy outcomes - Araban, marziyeh; Bahrami, nosrat; Karimian, zahra; khasaeiyan, somayeh (Advances in Nursing & Midwifery, 2013)
Abstract Introduction Outcomes of unintended pregnancies may endanger reproductive health. Studies have shown that women with unintended pregnancies are less likely to care for their health promotion activities, adequate nutrition and their fetus’ health.The objective of this cross sectional study was to compare unintended and intended pregnancy outcomes. Material and method A descriptive design was used for this study. A sample of 225 women attended to Tehran hospitals in 2007 were included in the study. Participants of the study were selected by stratified sampling method. An information form was used to collect data. Its validity and reliability were achieved by content and test-retest methods, respectively. Pregnancy outcomes including birth weight, height , head and chest circumference and Apgar score were investigated. Data analysis was done using SPSS 15 and t test, 2 and factor analysis. Results The mean age of participants was 25.86 (SD=4.6) years and 28% of participants reported their pregnancy as unintended. There was a significant association between unintended pregnancy and head circumference, p<0.05. Although, there were no significant association between unintended pregnancy and the other outcomes, these outcomes were poorer in the unintended pregnancy group as compared to the intended pregnancy group. Conclusion With regard to these results, it was hoped that the results of this study could emphasis on the efficiency of our data as a robust basis for future interventions regarding preventive strategies to decrease unintended pregnancy Key word: Sunintended pregnancy, birth weight, head circumference, chest circumference, Apgar score *Corresponding Author: Marziyeh Araban, Social determinants of health research center, Ahvaz Joundishapur University of medical sciences and health services. E-mail : Email:arabanm@ajums.ac.ir REFERENCES -Afshar M Delavar N Kinafar S (2004). Comparing growth indexes between unintended and intended pregnancies. Journal of Gorgan University of Medical Sciences. 6 (13) 40-45 -Aminshokravi F Haden CH (2004). Correlates of un intended pregnancies in a sample of Iranian women. Fertility and infertility. 5 (3) 249-258 -Araban M Kariman N Karimian Z (2006). Comparing birth outcomes in unintended and intended pregnancies. Abstract book of the first congress on innovation in nursing and midwifery. Qeshm. Iran -Arsalan O Mete S (2008). Pregnancy planning and antenatal health behavior: Findings from one Maternity unit in Turkey. Midwifery. 26 (3) 338-47 -Bahribinabaj N Bahribinabaj N Investigating the effect of unintended pregnancy on prenantal care visits (2002). Horizon of Medical Science. 8 (2) 75-80. Boroumand KH Saghafi Z Abedi A Bahadoran P (2005). Oucomes of un intended pregnancies. Abstract book of high risk pregnancy in Isfahan. P 14. Bayat H Asefzadeh S (2004). Prevalence of un-intended pregnancies and its relationship with low birth weight.Journal of Birjand University of Medical Sciences. 11 (1) 29-33. Blumenthal P Voedisch A Gemzell-Danielsson K (2011). Strategies to prevent unintended pregnancy: Increasing use of long-acting reversible contraception. Human Reproduction Update. 17 (1)121-37. -Furman S (1980) Unwanted pregnancy- the role of the general practitioner, South Africa Medical Journal, 58(23) 941- 942. -Gale CR O' Callaghan F Bredow M Marlynch N(2006). The in fluence of head growth in fetal growth in fetal life, In fancy and child heed on intelligence at the ages of 4 and 8 years. Pediatrics; 118(4) 1486-1492. -Gipson J Koenig M Hindin M (2008). The effect of unintended pregnancy on Infant, child and parental Health: A Review of the literature, studies in Family planning. 39(1) 18-38. -Hellerstedt W Pirieph L Lando H Curry S McBride C Grothaus L Nelson J (1998). Differences in pre conceptional and prenatal Behaviors in women with Intended and unintended pregnancies N American Journal public Health, 1998; 88: 663-666. -Haqiqi L Zand N Unintended pregnancies in women referring to Iran medical science university hospitals. Iran university of medical science journal. 9 (28) 33-38. -Iran far S Shakeri J Ranjbar Nazhadjafar P Rezaie M. (2005) Is un Intended pregnancy is a risk factor for depression in Iranian womens. Eeastern Mediterranean Health Journal. 11(4) 618-24. -Karmer S (2005). Maternal nutrition and adverse pregnancy outcome: Lessons from Epidemiology. Nestle Nutrition Workshop Series Paediatric Programme. 55:1-10; discussion 11-5. -Miller E Decker MR McCauley HL et al (2010). Pregnancy coercion, intimate partner violence and unintended pregnancy. Contraception. 81(4)316-22. Moghaddam banaem L Eftekhar H. The effect of unintended pregnancy on APGAR score. (2006). Journal of health faculty and health institute.2 (5) 73-78. Mohllajee A Curtis K Morrow B Marchbanks P (2007). Pregnancy intention and its relationship to birth and maternal outcomes. Obstetrics & Gynecology. 109(3)678-86 Najafi F Iranfar Sh Rezaee M Iranfar K (2012). A meta analysis of un intended pregnancy in Iran from 1374 to 1388.Behbood.16 (4)280-287. -Orr ST James SA Reitery P (2008). Unintended pregnancy and prenatal behaviors among urban, black women in Baltimore, Maryland: the Baltimore preterm birth study. Annals of epidemiology 18 (7) 545-51. Peyman N Heidarnia A GHofranipour F (2006). Association between perceived self-efficacy and reproductive behaviors among Iranian women referring to Mashahd health centers. Fertility and Infertility. 78-90 Pourheidari M Shamiyan N Souzani A (2004). Comparing quality of prenantal care and maternal-fetal morbidities in unintended and intended pregnancies.Abstract book of high risk pregnancy in Isfahan.p 19. Pourheidari M (B) Shameeiyan N (2004). Prevalence of unintended pregnancy and its determenint factor in SHahrood city.Payesh journal.6 (1) 63-70. –Singh S, Sedgh G Hussain R (2010). Unintended pregnancy: Worldwide levels, trends, and outcomes. Studies in Family Planning. 41(4) 241-50. -Pallito C, O'campo P (2004). The Relationship between intimate partner violence and unintended pregnancy analysis of a national sample from Colombia. International Family Planning Perspectives. 30 (4) 165-73. -Qian x Tang S Garner P (2004). Unintended pregnancy and Induced abortion among unmarried women in China: a systematic Review. BMC Health Services Research 2004, 4:1 -Ruow EI L HAAs J HABich J (1998). Timing of the influence of maternal nutrition status During pregnancy on fetal growth. American Journal of Human Biology. 10, 529-539 (1998). -Schemiege S Russ-NF (2005). Depression and unwanted first pregnancy: Longitudinal cohort study. BMJ 3: 331(7528) 1303. -Schwartz E Smith R Stenauer J Reeves M Caughey A (2007). Contraception 78 (2008) 204-208. The effect of unintended pregnancy on women's of life quality. -Silverman J Gupta J Decker M Kapur N R aj A (2007). Intimate partner violence and unwanted pregnancy, miscarriage, induced abortion, and still Birth among a national sample of Bangeladeshi women. BJOG an International Journal of Obstetrics and Gynecology. 114 (10) 1246-52. -Singh S Prada E Kes Her E (2006). Induced abortion and unintended pregnancy in Guatemala. International family planning perspectives. 32 (3) 136-45. -Thame M Wilks R MC Farien- Anderson N et al (1997). Relationship between maternal nutrition status and infant’s weight and body proportions at Birth. European Journal of Clinical Nutrition. 51(3) 134-138